2016
DOI: 10.1073/pnas.1606324113
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore vaccine conjugates protect against uropathogenicEscherichia coliurinary tract infection

Abstract: Uropathogenic Escherichia coli (UPEC) is the primary cause of uncomplicated urinary tract infections (UTIs). Whereas most infections are isolated cases, 1 in 40 women experience recurrent UTIs. The rise in antibiotic resistance has complicated the management of chronic UTIs and necessitates new preventative strategies. Currently, no UTI vaccines are approved for use in the United States, and the development of a highly effective vaccine remains elusive. Here, we have pursued a strategy for eliciting protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 61 publications
1
45
0
1
Order By: Relevance
“…Interestingly, the ferric iron(III)-dicitrate uptake determinant is contained in this soft core VF set. Scavenging iron is an important trait for mastitis pathogens, as the host sequesters iron by binding to high affinity molecules in the udder, like lactoferrin and citrate, and thus limiting bacterial growth by "nutritional immunity" [7,101,102]. Because citrate is the main iron-chelating mechanism found in milk during lactation, the Fec system was hypothesized to be the only essential iron transport system for MAEC growth in milk [32,34,35].…”
Section: Maec-enriched Orthologous Groups Are Mostly Associated With mentioning
confidence: 99%
“…Interestingly, the ferric iron(III)-dicitrate uptake determinant is contained in this soft core VF set. Scavenging iron is an important trait for mastitis pathogens, as the host sequesters iron by binding to high affinity molecules in the udder, like lactoferrin and citrate, and thus limiting bacterial growth by "nutritional immunity" [7,101,102]. Because citrate is the main iron-chelating mechanism found in milk during lactation, the Fec system was hypothesized to be the only essential iron transport system for MAEC growth in milk [32,34,35].…”
Section: Maec-enriched Orthologous Groups Are Mostly Associated With mentioning
confidence: 99%
“…These results could suggest that administration of adjuvants via our tested routes did not elicit an effective antibody response, and that cellular immunity may be involved in protection. To that point, we previously demonstrated that intranasal immunization with bacterial siderophores (yersiniabactin and aerobactin), that bind to our iron-receptor antigens, provides protection by an unknown non-antibody-mediated mechanism (16). In addition, experiments vaccinating mice with cholera toxin conjugated to outer-membrane iron receptors generated antigen-specific antibody universally, independent of any observed reduction in CFU during murine ascending UTI (28).…”
Section: Discussionmentioning
confidence: 99%
“…During the last 20 years there have been noteworthy advancements toward the development of a UTI vaccine, yet no licensed UTI vaccines are available for use in the U.S. Published studies have investigated the efficacy of vaccines containing O antigen (12), fimbrial subunits (13, 14), α-hemolysin (15), siderophores (16), and a variety of outer membrane siderophore receptors in animal models of UTI (1720). Human clinical trials have been performed on three vaccines, Uro-Vaxom, SolcoUrovac, and ExPEC4V.…”
Section: Introductionmentioning
confidence: 99%
“…Iron acquisition is well characterised as a key virulence determinant in ExPEC, with the ability to initiate a successful UTI completely abrogated in the absence of functional iron acquisition systems 43 . Recent experimental vaccine work exploiting siderophore production by ExPEC has shown to be highly effective in rodent models on ExPEC UTI 44 . The importance of iron acquisition can also explain many of the MDR efflux allele variants seen in this data set, with half occurring in the acrD gene which has been experimentally shown to play a role in iron acquisition in E. coli 45 .…”
Section: Discussionmentioning
confidence: 99%